Peripheral artery disease in Germany (2009-2018): Prevalence, frequency of specialized ambulatory care and use of guideline-recommended therapy - A population-based study - Christos Rammos; Martin Steinmetz; Julia Lortz; Amir A. Mahabadi; Olga Petrikhovich; Kristina Kirsch; Ramona Hering; Mandy Schulz; Tienush Rassaf (Elsevier, 2021)
Background: Peripheral artery disease (PAD) patients have high morbidity and mortality rates, demonstrating a need for improved treatment strategies. While underuse and undertreatment have been reported, there is no clear picture of patterns in population-level disease prevalence, prescription of guideline-recommended pharmacotherapy, or frequency of contact with dedicated specialists. We present population-level data on changes in prevalence, care and treatment of PAD from 2009 to 2018 in Germany. Methods: We analyzed the ambulatory claims data for all statutorily insured patients comprising 70.1 million patients each year and 87% of the German population. Prevalence was assessed by documentation of PAD and stratified by age and sex within the 10-year study timeframe. In addition, current ambulatory care, stratified by vascular specialists (vascular surgeons or angiologists), internists, cardiologists and primary care physicians, were examined. Findings: Prevalence increased from 1·85% in 2009 to 3·14% in 2018, affecting 2·3 million patients in 2018 and more males (55%) than females (45%). A low level of visits to vascular specialists, with 11·1% receiving care from vascular surgeons and 8·1% from angiologists, was shown. Moreover, analysis of guideline-recommended prescriptions revealed increasing, but still insufficient, prescription frequencies among PAD patients between 2009 and 2016, from 42·6% to 56% for statins and from 40·2% to 48·0% for antiplatelets. Interpretation: Our results show that the prevalence of PAD in Germany, as assessed by outpatient PAD documentation, is increasing and PAD patients are underutilizing specialized vascular care; moreover, the prescription frequency of guideline-recommended therapies remains low. There is a clear need to improve the referral and treatment algorithms in the high-risk PAD population. Funding: None.